The Role of Socio-Economic Background in Shaping Inequality Aversion: Evidence Based on Experimental Survey - VASQUEZ, ALEJANDRA ALICIA; Martin Leites (Usach, 2025)
This dataset supports the article ‘The Role of Socio-Economic Background in Shaping Inequality Aversion: Evidence Based on Experimental Survey.’ The purpose of the dataset is to provide the empirical information and codes necessary to reproduce the results of the study, which analyses how socio-economic background and informational frameworks influence inequality aversion (γ) among higher education students in Chile. The collection includes two databases and two analysis scripts. BBDD_1.dta corresponds to the database used in the econometric estimates of the paper, while BBDD_2_Graph.dta expands on the former by incorporating consistency variables used in the graphical analyses. Script1.do (Stata) runs the main econometric models, and Graphs.R (R) generates the distribution figures for the inequality aversion parameter. The dataset contains experimental choice variables, inequality aversion parameters (γ), informational treatment indicators, response consistency measures, demographic variables (age, gender, type of institution), among other additional variables. The dataset has a cross-sectional structure and integrates experimental and sociodemographic information collected through an experimental survey design applied in Santiago, Chile, between August 2023 and July 2024
Keywords: Psicología; Economía y Negocios; Sociología; Otras Ciencias Sociales; Inequality aversion; Consitency; Nepotism; Merit; Wealth; Socioeconomic background